Personality traits and pattern of beliefs of near-death(-like) experiencers - Bicego, Aminata; Cassol, Héléna; Simon, Jessica; Fritz, Pauline; Abagnale, Simona; Vanhaudenhuyse, Audrey; Laureys, Steven; Martial, Charlotte (Frontiers in Human Neuroscience, 2023)
Little is known about the potential personality and psychological predictors of near-death experiences (NDEs), and fewer yet those of NDEs-like (similar phenomenology reported after a non-life-threatening context). This study investigated whether personality traits (openness, extraversion, pleasantness, conscienciousness, and neuroticism), dissociative experiences, fantasy proneness, disposition towards auditory hallucinations, absorption trait and endorsement of paranormal and spiritual beliefs could be associated with the recall of NDEs(-like). To this aim, we invited four groups of people to retrospectively fill-in questionnaires assessing these factors: NDE experiencers (n=63), NDE(-like) experiencers (n=31), controls with a life-threatening situation but no NDE(-like) (n=43), and controls without a life-threatening situation nor a NDE(-like) (n=44). We carried out univariate analyses for each factor and then performed a multiple regression analysis and a discriminant analysis. The multivariate logistic regression analysis revealed that the endorsement of spiritual beliefs was associated with the recall of NDEs-like while openness and fantasy proneness were associated with the recall of NDEs. The discriminant analysis showed that these variables produce 35% of correct classification. Albeit retrospective, these results pave the way for future research on psychological predictors of NDEs(-like) by highlighting the influence of spirituality, openness and fantasy proneness on these phenomena.